Channel estimation based on compressed sensing in high-speed underwater acoustic communication - Guo, S.; He, Z.; Jiang, W.; Ou, Y.; Niu, K.; Rong, Yue; Caley, Michael; Duncan, Alec (IEEE, 2013)
The underwater acoustic (UA) channel is dispersive in both time and frequency with severe frequency-dependent signal attenuation. Efficient channel estimation and tracking are crucial to coherent high-rate UA communication. In this paper, we propose a new compressed sensing (CS) based channel estimation method with block-by-block channel tracking for UA communication. Compared with conventional channel estimation algorithms, the proposed method efficiently exploits the sparsity of the UA channel, and improves the channel tracking capability of UA communication system. The proposed algorithm was tested during our UA communication experiment conducted in December 2012 in the Indian Ocean off Rottnest Island, Western Australia. At a data rate of 8 kbps (QPSK constellations), average uncoded bit-error-rates (BERs) of 3% and 14% have been achieved over 1 km and 6 km ranges, respectively, using MMSE equalization based on the proposed channel estimation and tracking method.